A Study to Analyze the Paramount Way of Shade Selection among Restorative Dentists in South Canara District, Karnataka - Jain, Avni; Bhat, Vinaya; Hegde, Chethan (Journal of Health and Allied Sciences NU, 2017)
The most propelling force in dentistry today is the exigency for esthetic services. In today's dentistry restorations are expected to mimic not only the shade of natural dentition, but also the translucency, opacity, and shade distribution of real tooth. Our patients expect that the restoration can recreate nature perfectly, repeatedly and precipitously. Today's dentistry is mostly related to esthetic or expected to be esthetic by patients. No matter what type of restoration it is, it is expected to color match the existing teeth.In the present study subjects participated were faculty and post graduate doctors in the field of restorative dentistry in and around Mangalore city. A comprehensive questionnaire was used as a tool to gather the data which was analyzed later.
Keywords: Shade matching; color; esthetics